The new atheism : taking a stand for science and reason - Stenger, Victor J., 1935-2014 (Amherst, New York : Prometheus Books, 2009)
"In recent years a number of bestselling books have forcefully argued that belief in God can no longer be defended on rational or empirical grounds, and that the scientific worldview has rendered obsolete the traditional beliefs held by Christianity, Judaism, and Islam. The authors of these books have come to be known as the "New Atheists." Predictably, their works have been controversial and attracted a good deal of critical reaction." "In this new book, Victor J. Stenger reviews and expands upon the principles of New Atheism and answers many of its critics. He demonstrates in detail that naturalism - the view that all of reality is reducible to matter and nothing else - is sufficient to explain everything we observe in the universe, from the most distant galaxies to the inner workings of the brain that result in the phenomenon of mind." "Stenger disputes the claim of many critics that the question of whether God exists is beyond the ken of science. On the contrary, he argues that absence of evidence for God is, indeed, evidence of absence when the evidence should be there and is not."--BOOK JACKET.
Ingersoll's Vow -- 1. Atheism on the Offensive -- 2. The Folly of Faith -- 3. The Sword of Science -- 4. The Design Delusion -- 5. Holy Smoke -- 6. Suffering and Morality -- 7. The Nature of Nature -- 8. The Nature of Mind -- 9. The Way of Nature -- 10. The Future of Atheism.
Keywords: ATEISMO; RELIGION; CRISTIANISMO Y ATEISMO; RELIGION Y CIENCIA